Speculation Effects on Inflation in Iran Economy: TVP-FAVAR Model - Mohsen Khezri; Bahram Sahabi; Kazem Yavari; Hassan Heydari (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2015)
Given the importance of inflation in Iran economy, scrutiny of inflation determinants is important .according to various studies, evaluation of determinants of inflation using standard VAR model, may lead to wrong conclusions and this is due to omitted variables bias in VAR model. For example, the problem of price puzzle in the empirical literature is one of these results. In this study, for a more accurate assessment of determinants of inflation in Iranian economy and forecasting inflation, instead of using FAVAR model with constant coefficients, we have employed TVP-FAVAR models and inflation has been modeled. In this model, the variables of GDP growth, growth of the monetary base, inflation, exchange rates and interest rates are considered as the main variables, and to estimate the non-observable variables of speculation section return, variables in the overall classification are modeled. Based on the results, the relationship between the variables change over time and conditions prevailing in the economy is effective on the influence of model variables on each other.